Effects of L-carnitine and pentoxifylline on long-term preservation of the human sperms: An experimental study - Elham Aliabadi; Zohre Nateghian; Mohammad Hossein Nasr-Esfahani; Marziyeh Tavalaee; Tahereh Talaei-Khozani (International Journal of Reproductive BioMedicine)
Background: In infertility clinics, long-time preserving high-quality spermatozoa is a challenging problem.